ACM SIGGRAPH ASIA 2010 Sketches 2010
DOI: 10.1145/1899950.1899978
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized partial-body motion graphs

Abstract: Motion graphs are regarded as a promising technique for interactive applications. However, the graphs are generated based on the distance metric of whole body, which produce a limit set of possible transitions. In this paper, we present an automatic method to construct a new data structure that specifies transitions and correlations between partial-body motions, called Synchronized Partial-body Motion Graphs (SPbMGs). We exploit the similarity between lower-body motions to create synchronization conditions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Mousas et al overcome the synchronization problem by using velocity based temporal alignment. Partial‐body motion graphs can also be generated to splice and synchronize arm or hand motions with full‐body clips . For example, Majkowska et al integrate separately captured hand motions into full body animation and find the corresponding splicing points using a two‐pass dynamic time warping algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Mousas et al overcome the synchronization problem by using velocity based temporal alignment. Partial‐body motion graphs can also be generated to splice and synchronize arm or hand motions with full‐body clips . For example, Majkowska et al integrate separately captured hand motions into full body animation and find the corresponding splicing points using a two‐pass dynamic time warping algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Several other techniques have been developed that take into account body part dependencies, such as that of Ma et al [10], who applied motion splicing to model motion variation, and Mousas and Newbury [18] who used motion layers for splicing the lowe-, upper-, and hand-body parts. Finally, Tamada et al [11] and Ng et al [12] designed splicing motions associated with a resultant motion derived from motion graphs, giving the ability to generate long animation sequences in which partial motions appear at specified time steps.…”
Section: Related Workmentioning
confidence: 99%
“…based on motion interpolation) [5]. Recently, it is suggested that by decomposing whole body motion sequences into their upper and lower body parts, the reusability of motion sequences can be improved since there are more choices for motion synthesis [6] [7]. However, splicing upper and lower body motion sequences back to a whole body one is never trivial.…”
Section: Introductionmentioning
confidence: 99%